The Gothenburg SOM Survey 2020 - SOM Institute, University of Gothenburg (University of Gothenburg, 2022)
In the autumn of 2020, the fifth edition of the Gothenburg SOM survey was conducted. A total of 8 000 randomly selected citizens of Gothenburg answered questions about attitudes and habits in relation to society, opinion and media. Many of the questions in the Gothenburg survey are of a regional nature, and concern local politicians and infrastructure initiatives.

Hösten 2020 genomfördes för femte gången en SOM-undersökning i Göteborgs stad, där totalt 8 000 slumpmässigt utvalda göteborgare fick svara på frågor om attityder och vanor i relation till samhälle, opinion och medier. Många av frågorna i Göteborgsundersökningen är av regional karaktär och rör lokala politiker, infrastruktursatsningar, och bilden av Göteborg som stad.
SOM-undersökningen i Göteborg 2020
Keywords: housing; boende; occupations; yrken; public sector; offentlig sektor; environment; miljö; consumption; konsumtion; public opinion; allmän opinion; environmental degradation; miljöförstörelse; trust; förtroende; european union; europeiska unionen; political interest; politiskt intresse; local government services; kommunal service; public transport; kollektivtrafik; medical care; sjukvård; public services; offentlig service; news; nyheter; privatization; privatisering; income; inkomst; political participation; politiskt deltagande; sick leave; sjukfrånvaro; religious practice; religionsutövning; democracy; demokrati; internal politics; inrikespolitik; political parties; politiska partier; Dental Care; Tandvård; internet use; internetanvändning; politicians; politiker; local government organizations; kommunala organisationer; social participation; socialt deltagande; working conditions; arbetsförhållanden; households; hushåll; local community facilities; lokala serviceinrättningar; clubs; föreningar; cultural activities; kulturaktiviteter; leisure time activities; fritidsaktiviteter; educational levels; utbildningsnivå; traffic; trafik; political attitudes; politiska åsikter; state health services; statlig hälso- och sjukvård; social networks; socialt nätverk; CORS; CORS; POLITICS; POLITIK; SOCIETY AND CULTURE; SAMHÄLLE OCH KULTUR; Elections; Val; Political behaviour and attitudes; Politiska beteenden och attityder; Political ideology; Politisk ideologi; Cultural activities and participation; Kulturaktiviteter och deltagande; Media; Media; MEDIA, COMMUNICATION AND LANGUAGE; MEDIA, KOMMUNIKATION OCH SPRÅK; LABOUR AND EMPLOYMENT; ARBETE OCH SYSSELSÄTTNING; Leisure, tourism and sport; Fritid, turism och sport